Effect of antioxidants on histamine receptor activation and sustained post-exercise vasodilatation in humans - Romero, Steven A. (Exp Physiol, 2015)
An acute bout of aerobic exercise elicits a sustained post-exercise vasodilatation that is mediated by histamine H(1) and H(2) receptor activation. However, the upstream signaling pathway that leads to post-exercise histamine receptor activation is unknown. We tested the hypothesis that the potent antioxidant ascorbate would inhibit this histaminergic vasodilatation following exercise. Subjects performed 1 hr unilateral dynamic knee extension at 60% of peak power in three conditions: 1) control; 2) intravenous ascorbate infusion; and, 3) ascorbate infusion plus oral H(1)/H(2) histamine receptor blockade. Femoral artery blood flow (Doppler ultrasound) was measured before exercise and for 2 hr post-exercise. Femoral vascular conductance was calculated as flow/pressure. Post-exercise vascular conductance was greater for control condition (3.4 ± 0.1 ml min(−1) mmHg(−1)) compared with ascorbate (2.7 ± 0.1 ml min(−1) mmHg(−1), P < 0.05) and ascorbate plus H(1)/H(2) blockade (2.8 ± 0.1 ml min(−1) mmHg(−1), P < 0.05), which did not differ from one another (P = 0.9). Because ascorbate may catalyze the degradation of histamine in vivo, we conducted a follow-up study where subjects performed exercise in two conditions: 1) control and 2) intravenous N-acetylcysteine infusion. Post-exercise vascular conductance was similar for control (4.0 ± 0.1 ml min(−1) mmHg(−1)) and N-acetylcysteine conditions (4.0 ± 0.1 ml min(−1) mmHg(−1); P = 0.8). Thus, the results in study 1 were due to the degradation of histamine in skeletal muscle by ascorbate, since the histaminergic vasodilatation was unaffected by N-acetylcysteine. Taken together, exercise-induced oxidative stress does not appear to contribute to sustained post-exercise vasodilatation.